The analysis on the seismic behavior of T-shaped prefabricated special-shaped CFST with rectangular multi-cell columns. (December 2020) - Cui, Wenbin; Wang, Lai; Chen, Huirong; Chen, Haitao; Liu, Su
Abstract: For an in-depth understanding of the seismic behavior of shaped columns, a kind of T-shaped prefabricated special-shaped concrete-filled steel tubular with rectangular multi-cell columns was proposed in this paper. Furthermore, three specimens of full scale were designed and produced for low cyclic reversed loading and their failure morphology, hysteresis curve and P-Δ curve were obtained. The experimental results showed that the failure of the specimen was the bulking and cracking of the steel tube at the bottom of column along the loading axis, the powdery concrete dropped and finally the specimen failed to work. In addition, ABAQUS was used to perform finite element simulation on the three specimens in the experiment to verify the rationality and feasibility of the simulation. In this paper, by changing the axial compression ratio, concrete grade, steel grade, section height to thickness ratio and loading direction, the P-Δ curve, stiffness degradation, ductility and energy dissipation capacity of models under different parameters were analyzed for seismic performance. The simulation results showed that higher axial compression ratio leads to lower ultimate bearing capacity and ductility. With the increase of concrete grade, steel grade and section height to thickness ratio, the ultimate bearing capacity of the model increased but the ductility decreased. The shaped column specimens loaded in the 45° direction have higher bearing capacity, better ductility and seismic performance.